The sequence 0, 2, 8, 30, 112, 418,... is defined recursively by a_0 = 0, a_1 = 2, a_(n+1) = 4a_n-a_(n-1). What is the formula for a general term a_n?

1 Answer
Sep 16, 2016

a_n =((2+sqrt(3))^n - (2-sqrt(3))^n)/sqrt(3)

Explanation:

color(white)()
Proof by induction

Case n=0

((2+sqrt(3))^0 - (2-sqrt(3))^0)/sqrt(3) = (1 - 1) / sqrt(3) = 0 = a_0

Case n=1

((2+sqrt(3))^1 - (2-sqrt(3))^1)/sqrt(3) = (2sqrt(3))/(sqrt(3)) = 2 = a_1

Induction step

Note that (2-sqrt(3))(2+sqrt(3)) = 2^2-(sqrt(3))^2 = 4-3 = 1

So:

((2+sqrt(3))^(n+1)-(2-sqrt(3))^(n+1))/sqrt(3)

=((2+sqrt(3))(2+sqrt(3))^n-(2-sqrt(3))(2-sqrt(3))^n)/sqrt(3)

=(4((2+sqrt(3))^n-(2-sqrt(3))^n)-((2-sqrt(3))(2+sqrt(3))^n-(2+sqrt(3))(2-sqrt(3))^n))/sqrt(3)

=(4((2+sqrt(3))^n-(2-sqrt(3))^n))/sqrt(3)-((2+sqrt(3))^(n-1)-(2-sqrt(3))^(n-1))/sqrt(3)

=4a_n-a_(n-1)

color(white)()
Bonus

3a_n^2+4 is always the square of an integer ...

Note that (2+sqrt(3))^n(2-sqrt(3))^n = 1^n = 1

So:

3a_n^2+4 = 3(((2+sqrt(3))^n - (2-sqrt(3))^n)/sqrt(3))^2 + 4

color(white)(3a_n^2+4) = ((2+sqrt(3))^n - (2-sqrt(3))^n)^2 + 4

color(white)(3a_n^2+4) = (2+sqrt(3))^(2n) - 2(2+sqrt(3))^n(2-sqrt(3))^n+(2-sqrt(3))^(2n) + 4

color(white)(3a_n^2+4) = (2+sqrt(3))^(2n) + 2(2+sqrt(3))^n(2-sqrt(3))^n+(2-sqrt(3))^(2n)

color(white)(3a_n^2+4) = ((2+sqrt(3))^n + (2-sqrt(3))^n)^2

Note that (2+sqrt(3))^n+(2-sqrt(3))^n must be an integer, since odd powers of sqrt(3) from the two binomial powers carry opposite signs.